The profile of comorbities in patients with COVID-19 in the municipality of Parnaíba-PI (Research, Society and Development, 2023)
COVID-19 can affect individuals of any age, but usually the most serious conditions are related to people over 60 years of age and/or with comorbidities, such as systemic arterial hypertension, diabetes and obesity, because in addition to these conditions they lead to structural changes, the Treatment itself may predispose individuals to a greater risk of infection. The objective of the study is to outline the clinical-epidemiological profile of patients with a confirmed case of COVID-19 who had at least one comorbidity in the municipality of Parnaíba, Piauí. This is an epidemiological study carried out through the analysis of data extracted from the flu syndrome investigation form, after applying the inclusion and exclusion criteria of research participants, the study sample was completed in 684 patients. Most were female (61.25%), with a predominance between 18 and 30 years old (29.58%), followed by 31 to 45 years old (27.65%). Of these patients, 79.25% evolved to cure and 8.06% to death. Regarding deaths, there was a predominance of deaths in males, over 60 years old and with at least one comorbidity, the conditions most related to death cardiovascular disease, diabetes and respiratory disease. The presence of comorbidity is an unfavorable prognosis, namely: severe acute respiratory syndrome (SARI), admission to the Intensive Care Unit (ICU), need for invasive mechanical ventilation, cardiac abnormalities and death. A large number of underreported or incorrectly registered cases were observed, which may hinder the epidemiological characterization and disease control strategies.